Przesłanka faktyczna konsensualnych sposobów zakończenia postępowania karnego na tle art. 335 i 338a k.p.k. - Woźniewski, Krzysztof (Ius et Administratio, 2016)
This article indicates the theoritical aspects of concept of evidential basis of prosecutor procedural motions to the court in order to sentence the accused without a trial. There are two kind of such prosecutors’ motions described in art. 335 of polish criminal procedure code. The first one is submitted by the prosecutor to the court instead of formal bill of indictment (art. 335 § 1) and the second one is submitted as a supporting document of formal bill of indictment (art. 335 § 2). In the first case the prosecutor is allowed to submit such motion if the suspect person the accused pleads guilty, and in the light of his explanations circumstances of the crime and the guilt is not in doubt, in second - if the circumstances of the crime and the guilt of the accused is not in doubt and a statement of evidence submitted by the accused are not inconsistent with the established facts. The third possibility to conclude the criminal case avoiding the full trial is the formal request of accused person to be sentenced to a penalty or a penal measure without the conduct of evidentiary proceedings submitted before the service of the notification of the date of the trial ( art. 338a) and it is granted if the circumstances of the offence do not raise doubts.